Mixture sheet for electrochemical device, electrochemical device, and method for manufacturing mixture sheet for electrochemical device

JP2025036341AActive Publication Date: 2025-03-14DAIKIN INDUSTRIES LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024147705
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14
Estimated Expiration
2044-08-29

AI Technical Summary

Benefits of technology

【0024】 本開示によれば、電気化学特性を良好に維持しながら、シート強度を改善できる電気化学デバイス用合剤シート、電気化学デバイス、及び、電気化学デバイス用合剤シートの製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036341000001
    Figure 2025036341000001
  • Figure 2025036341000002
    Figure 2025036341000002
  • Figure 2025036341000003
    Figure 2025036341000003
Patent Text Reader

Abstract

To provide a mixture sheet for an electrochemical device which can improve sheet strength while satisfactorily maintaining electrochemical characteristics, an electrochemical device, and a method for manufacturing a mixture sheet for an electrochemical device.SOLUTION: A mixture sheet for an electrochemical device contains a silicone compound which is liquid at 25°C, a binder and an electrochemical device material, wherein a content of the silicone compound is 0.5 to 20 mass% with respect to a solid content of the mixture sheet for electrochemical device, and kinetic viscosity at 25°C of the silicone compound is 5 cSt to 60,000 cSt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a mixture sheet for an electrochemical device, an electrochemical device, and a method for producing a mixture sheet for an electrochemical device. [Background technology]

[0002] 2. Description of the Related Art With the trend toward lighter and smaller electric appliances in recent years, the development of electrochemical devices having high energy density, such as lithium ion secondary batteries, has progressed.

[0003] As technologies relating to electrochemical devices, Patent Document 1 discloses an electrode for a secondary battery using a powdered active material, a conductive material, and a fluorine-containing polymer resin, and Patent Document 2 discloses a self-supporting solid composite electrolyte membrane using solid ion-conductive inorganic particles and a tetrafluoroethylene (co)polymer. Patent Document 3 discloses a solid electrolyte slurry and an electrode slurry containing an inorganic solid electrolyte material and a liquid inert to the inorganic solid electrolyte material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-026984 A [Patent Document 2] Special Publication No. 2022-546129 [Patent Document 3] JP 2016-062709 A Summary of the Invention [Problem to be solved by the invention]

[0005] When a mixture sheet for electrochemical devices is produced using a slurry such as that of Patent Document 3, there is an advantage that a large-area sheet can be obtained, but it tends to be difficult to obtain the sheet strength required for handling (transporting, etc.) the sheet in the manufacturing process. In addition, by increasing the amount of binder, it becomes possible to obtain the sheet strength required in the manufacturing process, but electrochemical properties such as discharge capacity tend to decrease. Thus, with conventional methods, it has been difficult to obtain a mixture sheet for electrochemical devices that has both electrochemical properties and sheet strength.

[0006] An object of the present disclosure is to provide a mixture sheet for electrochemical devices, which can improve sheet strength while maintaining good electrochemical properties, an electrochemical device, and a method for manufacturing a mixture sheet for electrochemical devices. [Means for solving the problem]

[0007] The present disclosure (1) is a mixture sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, wherein the content of the silicone compound is 0.5 to 20 mass % relative to a solid content of the mixture sheet for electrochemical devices, and the kinetic viscosity of the silicone compound at 25° C. is 5 cSt to 60,000 cSt.

[0008] The present disclosure (2) is a mixture sheet for electrochemical devices according to the present disclosure (1), wherein the silicone compound has a polyoxyalkylene chain.

[0009] The present disclosure (3) is the mixture sheet for electrochemical devices according to the present disclosure (1) or (2), wherein the content of the silicone compound is 0.5 to 15 mass % based on the solid content of the mixture sheet for electrochemical devices.

[0010] The present disclosure (4) is a mixture sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, wherein the silicone compound has a polyoxyalkylene chain.

[0011] The present disclosure (5) is a mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (4), wherein the silicone compound has a saturated water content at 25° C. of more than 30 ppm.

[0012] The present disclosure (6) is a mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (5), wherein the silicone compound has a mass loss rate of 20 mass % or less when heated at 150° C. for 24 hours.

[0013] The present disclosure (7) is a mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (6), characterized in that the content of the binder is 0.5 to 10 mass % with respect to the solid content of the mixture sheet for electrochemical devices.

[0014] The present disclosure (8) is a mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (7), which contains a metal salt.

[0015] The present disclosure (9) is the mixture sheet for electrochemical devices according to the present disclosure (8), wherein the content of the metal salt relative to the silicone compound is 0.1 to 30 mass %.

[0016] The present disclosure (10) is a mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (9), wherein the mixture sheet for electrochemical devices is an electrode mixture sheet or an electrolyte mixture sheet.

[0017] The present disclosure (11) is a mixture sheet for an electrochemical device according to any one of the present disclosures (1) to (10), in which the binder is a fluorine-based polymer material.

[0018] The present disclosure (12) is a mixture sheet for electrochemical devices according to the present disclosure (11), wherein the binder is at least one selected from the group consisting of polytetrafluoroethylene, poly(vinylidene fluoride-co-hexafluoropropylene), and poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene).

[0019] The present disclosure (13) is the mixture sheet for electrochemical devices according to the present disclosure (12), wherein the binder is polytetrafluoroethylene.

[0020] The present disclosure (14) is a mixture sheet for electrochemical device according to any one of the present disclosures (1) to (13), which contains a conductive assistant.

[0021] The present disclosure (15) is an electrochemical device using the mixture sheet for electrochemical devices according to any one of the present disclosures (1) to (14).

[0022] The present disclosure (16) relates to a method for producing a mixture sheet for electrochemical devices, the method including: a step (1) of mixing a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material; and a step (2) of rolling the mixture for electrochemical devices obtained in the step (1) into a sheet.

[0023] The present disclosure (17) is the manufacturing method according to the present disclosure (16), wherein the silicone compound has a kinetic viscosity of 5 cSt to 60,000 cSt at 25° C., the silicone compound has a polyoxyalkylene chain, and the binder is polytetrafluoroethylene. Effect of the Invention

[0024] According to the present disclosure, it is possible to provide a mixture sheet for electrochemical devices, which can improve sheet strength while maintaining good electrochemical properties, an electrochemical device, and a method for manufacturing a mixture sheet for electrochemical devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present disclosure will now be described in detail.

[0026] <Compound sheet for electrochemical devices> The first present disclosure relates to a mixture sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, wherein the content of the silicone compound is 0.5 to 20 mass % relative to a solid content of the mixture sheet for electrochemical devices, and the kinetic viscosity of the silicone compound at 25° C. is 5 cSt to 60,000 cSt.

[0027] Since the first electrochemical device mixture sheet of the present disclosure has the above-mentioned configuration, it is possible to improve the strength of the electrode sheet or solid electrolyte sheet while maintaining good electrochemical properties. This is thought to be because the silicone compound imparts fluidity to the electrochemical device material during sheet molding, thereby enabling the molding of a uniform sheet. In particular, when the binder contains a fibrillating resin, it is thought that the strength is improved because the flow deformation during molding promotes the generation of fibrils. In addition, the silicone compound imparts fluidity to the electrochemical device material during sheet molding, thereby improving the sheet strength, and therefore it is possible to reduce the amount of binder used and improve the energy density of the electrochemical device.

[0028] The silicone compound is liquid at 25°C and has a kinetic viscosity at 25°C of 5 cSt to 60,000 cSt. If the kinetic viscosity is too low, the silicone compound may flow out during pressure molding, and if it is too high, sufficient fluidity may not be imparted to the electrochemical device material, and the sheet strength may not be improved. From the viewpoint of imparting fluidity to the electrochemical device material, the kinetic viscosity is preferably 10 cSt or more, more preferably 100 cSt or more, and is preferably 20,000 cSt or less, more preferably 10,000 cSt or less. In this specification, the above kinematic viscosity is a value determined using an Ubbelohde viscometer at 25° C. based on ASTM D445-46T.

[0029] The silicone compound is not particularly limited as long as it has a siloxane bond, but it is preferable that the silicone compound has a polyoxyalkylene chain in addition to the siloxane bond. Examples of the constituent units of the polyoxyalkylene chain include oxyethylene, oxypropylene, oxybutylene, etc. The ratio of these is not particularly limited.

[0030] The silicone compound tends to have a higher polarity as it has a higher affinity with water molecules, that is, as its saturated water content is higher. When the silicone compound has a high polarity, it is less likely to cause a decrease in electrochemical properties such as discharge capacity. This is believed to be because ions can move in the silicone compound. From this perspective, the silicone compound preferably has a saturated water content of more than 30 ppm at 25°C, more preferably 50 ppm or more, and even more preferably 100 ppm or more. There is no particular upper limit, but when the silicone compound does not have a polyoxyalkylene chain, it is usually 1000 ppm or less. In this specification, the saturated water content is measured by the following method. The silicone compound is mixed with 5 times the volume of water to obtain a mixture, and the mixture is stirred and then left to stand at 25°C for 24 hours. The mixture is then centrifuged to separate into an aqueous phase and a thick phase of the silicone compound, and the thick phase is measured using Karl Fischer titration. A Karl Fischer moisture meter (MKC-610 (Kyoto Electronics Manufacturing Co., Ltd.)) and Aquamicron AX (Mitsubishi Chemical Co., Ltd.) are used as Karl Fischer reagents to measure the moisture content, and the sample amount is 1g. If the silicone compound has a polyalkylene chain, it is miscible with water, so the saturated moisture content is considered to be infinite.

[0031] If the silicone compound has a large water content, the electrochemical device material may be deteriorated by the water, and the electrochemical properties may be impaired. Therefore, it is preferable to use the silicone compound after dehydration treatment. The dehydration treatment is not particularly limited, but for example, the silicone compound is placed in an evaporator and 1.0×102 One example of a method is drying the film for 3 to 6 hours while heating in an oil bath at 80 to 150°C and 100 Pa. The moisture content of the silicone compound after drying is preferably 150 ppm or less, more preferably 100 ppm or less. The lower limit is not particularly limited and may be 0 ppm, but is usually 10 ppm or more. In this specification, the water content is measured by Karl Fischer titration.

[0032] The electrochemical device mixture sheet of the first disclosure may be manufactured through a process involving heating, such as hot molding, but if the silicone compound volatilizes due to heating, sufficient improvement effects may not be obtained. In addition, if the silicone compound volatilizes, air bubbles may be generated in the sheet, resulting in a defective product. Therefore, it is preferable that the silicone compound is not easily volatilized. From this viewpoint, the mass loss rate of the silicone compound when heated at 150°C for 24 hours is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. The lower limit is not particularly limited and may be 0% by mass, but is usually 0.5% by mass or more. In this specification, the mass reduction rate is measured by the following method. 5 g of the silicone compound is weighed into an aluminum cup (diameter 50 mm, height 12 mm) and heated in a hot air circulating oven at 150°C for 24 hours, and the mass is measured before and after, and calculated according to the following formula. A sample is taken three times, and the calculation is performed for each, and the average value is calculated and used. Mass reduction rate (mass%) = [(mass (g) of silicone compound before heating) - (mass (g) of silicone compound after heating)] / (mass (g) of silicone compound before heating) x 100

[0033] The silicone compound preferably has an ionic conductivity of 1.0×10 -9 S / cm or more, preferably 1.0×10 -8 S / cm or more, more preferably 1.0×10 -7The upper limit is not particularly limited, but is preferably 1.0×10 -3 S / cm or less. The above ionic conductivity is a value obtained by measuring at 25° C. using a Mettler Toledo SevenCompact S230. The measuring device is calibrated in advance using a standard solution of 12.88 mS / cm before use.

[0034] From the viewpoint of imparting fluidity to the electrochemical device material, the content of the silicone compound is 0.5 to 20 mass % relative to the solid content of the electrochemical device mixture sheet, and the content is preferably 1 mass % or more, more preferably 5 mass % or more, and is preferably 15 mass % or less, more preferably 10 mass % or less. The above content does not refer to the amount of the silicone compound added, but to the amount extracted from the electrochemical device mixture sheet.

[0035] In this specification, the solid content of the electrochemical device mixture sheet is a component that is given fluidity by the silicone compound and is solid after mixing with the silicone compound. The solid content does not include substances (metal salts, etc.) that dissolve in the silicone compound after mixing. In the examples described later, the active material, the conductive assistant, and the binder correspond to the solid content.

[0036] As the binder, a fluorine-based polymer material, a non-fluorine-based polymer material, or the like can be used.

[0037] Examples of the non-fluorinated polymer material include polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, nitrocellulose, SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, NBR (acrylonitrile-butadiene rubber), ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or hydrogenated product thereof, EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-styrene copolymer, styrene-isoprene-styrene block copolymer or hydrogenated product thereof, syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, and polymer compositions having ionic conductivity for alkali metal ions (particularly lithium ions).

[0038] Examples of the fluorine-based polymer material include a polymer having a fluorine-containing monomer such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), vinylidene fluoride (VdF), perfluoroalkyl vinyl ether (PAVE), chlorotrifluoroethylene (CTFE), trifluoroethylene, trifluoropropylene, tetrafluoropropylene, pentafluoropropylene, trifluorobutene, tetrafluoroisobutene, hexafluoroisobutene, vinyl fluoride, iodine-containing fluorinated vinyl ether, General formula (1-1)CH 2 =CFRf 1 (In the formula, Rf 1 is a linear or branched fluoroalkyl group having 1 to 12 carbon atoms), and General formula (2-1)CHF=CHRf 2 (Rf 2is at least one polymer selected from the group consisting of fluorine-containing monomers represented by a straight-chain or branched fluoroalkyl group having 1 to 12 carbon atoms. The above polymer may be copolymerized with at least one monomer selected from the group consisting of fluorine-free monomers such as ethylene (Et), propylene (Pr) and alkyl vinyl ethers, monomers that provide crosslinkable groups (cure sites) and reactive emulsifier monomers, as necessary.

[0039] The monomer that provides the crosslinkable group is not particularly limited as long as it provides a polymer with a crosslinking site for forming a crosslink with a crosslinking agent. For example, CF 2 =CFOCF 2 CF(CF 3 )OCF 2 CF 2 C.N., C.F. 2 =CFOCF 2 CF(CF 3 )OCF 2 CF 2 COOH, CF 2 =CFOCF 2 CF(CF 3 )OCF 2 CF 2 CH 2 I, C.F. 2 =CFOCF 2 CF 2 CH 2 I, C.H. 2 =CFCF 2 OCF(CF 3 )CF 2 OCF(CF 3 )CN, CH 2 =CFCF 2 OCF(CF 3 )CF 2 OCF(CF 3 )COOH, CH 2 =CFCF 2 OCF(CF 3 )CF 2 OCF(CF 3 )CH 2 OH, CH 2 =CHCF 2 CF 2 I, C.H. 2 =CH(CF2 ) 2 CH=CH 2 , C.H. 2 =CH(CF 2 ) 6 CH=CH 2 , C.F. 2 =CFO(CF 2 ) 5 CN is one example.

[0040] The reactive emulsifier monomer is not particularly limited as long as it is a compound having at least one unsaturated bond and at least one hydrophilic group. For example, 2 =CFCF 2 OCF(CF 3 )CF 2 OCF(CF 3 )COONH 4 , C.H. 2 =CFCF 2 CF(CF 3 )OCF 2 CF 2 COONH 4 , C.F. 2 =CFOCF 2 CF(CF 3 )OCF(CF 3 )COONH 4 Examples include:

[0041] The binders may be used alone or in any combination of two or more in any ratio.

[0042] The binder is preferably the above-mentioned fluorine-based polymer material, and in particular, at least one selected from the group consisting of polytetrafluoroethylene (PTFE), poly(vinylidene fluoride-co-hexafluoropropylene) and poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene), and more preferably PTFE.

[0043] The binder may be a combination of two or more of the above fluorine-based polymer materials, and a combination of PTFE and a fluorine-based polymer material other than PTFE is preferred. In particular, a combination of at least one selected from the group consisting of PTFE and poly(vinylidene fluoride-co-hexafluoropropylene) and PTFE and poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene) is preferred.

[0044] When the binder contains PTFE, the PTFE content in the binder is preferably 50% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, and particularly preferably 85% by mass or more. The upper limit of the PTFE content in the binder is not particularly limited, and may be 100%.

[0045] In addition, fibrillary resins can also be used as the binder. The fibrillary resins are resins that are easily fibrillated when shear stress is applied, and examples of such resins include liquid crystal polymers (LCPs), cellulose, acrylic resins, ultra-high molecular weight polyethylene, and PTFE. Among these, PTFE is preferred from the standpoints of chemical stability, thermal stability, and processability.

[0046] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. As the PTFE, the modified PTFE is preferred in that it improves the binding force, sheet strength and flexibility.

[0047] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving the binding force, sheet strength, and flexibility. The lower limit of the modified monomer unit content is preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and even more preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, and even more preferably 0.30% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0048] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0049] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0050] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF 2 =CF-ORff(A) (wherein Rff represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0051] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rff in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0052] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0053] The perfluorovinyl ether further includes those in which, in the above general formula (A), Rff is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rff is the following formula:

[0054] [ka]

[0055] (wherein m represents 0 or an integer of 1 to 4), Rff is a group represented by the following formula:

[0056] [ka]

[0057] (wherein n represents an integer of 1 to 4).

[0058] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0059] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF 2 =CF-CF 2 -ORff1 (B) (In the formula, Rff 1 represents a perfluoro organic group.

[0060] Rff 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. 2 =CF-CF 2 -O-CF 3 , C.F. 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 At least one selected from the group consisting of CF 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 More preferably, at least one selected from the group consisting of CF 2 =CF-CF 2 -O-CF 2 CF 2 CF 3 is more preferred.

[0061] As the modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the composite sheet, at least one selected from the group consisting of PAVE, HFP, VDF, and CTFE is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) [PMVE], HFP, VDF, and CTFE is more preferable.

[0062] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0063] Examples of PTFE that are commonly available on the market include F-104, F-106, F-107, F-104C, F-121, F-201, F-205, F-208, and F-302 manufactured by Daikin Industries, 60X, 601X, 602X, 605XTX, 613AX, 62X, 62NX, 62XTX, 640XTX, 641XTX, 650XTX, 669X, 669NX, 6CX, 6CNX, CFP6000X, 6J, 6CJ, 62J, 640J, and 641J manufactured by Chemours, and T manufactured by 3M. F2029, TF2025Z, TF2053Z, TF2073Z, TF2001Z, TF2071USZ, TF2072Z, etc., CD145, CD123, CD126E, CD097, CD084E, CD086EL, CD086EH, CD090E, CD122E, CD141E, CD127E, etc., manufactured by AGC, and DF681F, DF680F, DF330F, DF291F, DF230F, DF210F, DF132F, DF130F, DF120F, etc., manufactured by Solvay.

[0064] In terms of being able to form a composite sheet having even greater strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0065] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0066] In order to obtain good sheet strength, the content of the binder is preferably 0.5 mass % or more, more preferably 1 mass % or more, and even more preferably 2 mass % or more, relative to the solid content of the electrochemical device composite sheet, and is preferably 10 mass % or less, more preferably 8 mass % or less, and even more preferably 5 mass % or less.

[0067] The content of the binder is the amount added when the amount added during the production of the mixture sheet for electrochemical devices is known, but when the amount added is unknown, it can be calculated, for example, by the following method. When a good solvent is present in the binder, the good solvent is added in an amount about 10 times the volume of the powder obtained by pulverizing the electrochemical device composite sheet and stirred for 24 hours to obtain an extract, which is then filtered. The amount of the binder present in the obtained filtrate is regarded as the content of the binder. When there is no good solvent for the binder, for example, as described in

[0051] of WO 2023 / 119814, the amount of residue remaining after a process for dissolving and removing everything other than the binder is regarded as the content of the binder.

[0068] As the electrochemical device material, for example, an electrode active material can be used. That is, the mixture sheet for electrochemical devices according to the first present disclosure may be an electrode mixture sheet containing an electrode active material.

[0069] The electrode material may be a positive electrode active material or a negative electrode active material.

[0070] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.

[0071] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O 4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), in which M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0072] Among these, MCoO is particularly noteworthy because it can provide electrochemical devices with high energy density and high output. 2 , M.M.N.O. 2 , MNiO 2 , M.M.n 2 O 4 , M.N.I. 0.8 Mn 0.1 Co 0.1 O 2 , M.N.I. 0.8 Co 0.15 Al 0.05 O 2 , or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc. are preferred, and the compound represented by the following general formula is preferred. 0.8 Mn 0.1 Co 0.1 O 2 is particularly preferred. MNi h Co i Mn j M 5 k O 2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0073] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO 4 ) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0074] The transition metal of the alkali metal-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, or the like. Specific examples include LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 , LifeP 2 O 7 Iron phosphates such as LiCoPO 4 and lithium transition metal phosphate compounds in which a part of the transition metal atoms constituting the main part of the lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. As the lithium-containing transition metal phosphate compound, those having an olivine structure are preferable.

[0075] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O 2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0076] Other positive electrode active materials include MFePO 4 , M.N.I. 0.8 Co 0.2 O 2 , M 1.2 Fe 0.4 Mn 0.4 O 2 , M.N.I. 0.5 Mn 1.5 O 2 , M.V. 3 O 6 , M 2 MnO 3 In particular, M 2 MnO 3 , M.N.I. 0.5 Mn 1.5 O 2 The positive electrode active materials such as the above are preferable in that the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or a voltage of 4.6 V or more. Therefore, electrochemical devices such as secondary batteries using positive electrode materials containing the above-mentioned positive electrode active materials are preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.

[0077] Other positive electrode active materials include M 2 MnO 3 and M.M. 6 O 2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 Also included are solid solution materials with transition metals such as Co, Ni, Mn, and Fe.

[0078] The solid solution material is, for example, a material represented by the general formula M x [Mn (1-y) M 7 y ]O zIt is an alkali metal manganese oxide represented by the following formula. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and includes, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the ranges of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O 2 A manganese-containing solid solution material such as Li 2 MnO 3 with LiNiO 2 or LiCoO 2 solid-solved therein is preferable in that it can provide an alkali metal ion secondary battery having a high energy density.

[0079] Also, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferably used by mixing it with the above positive electrode active material. The amount of lithium phosphate used is preferably at least 0.1% by mass, more preferably at least 0.3% by mass, and still more preferably at least 0.5% by mass with respect to the total of the above positive electrode active material and lithium phosphate, and the upper limit is preferably at most 10% by mass, more preferably at most 8% by mass, and still more preferably at most 5% by mass.

[0080] Also, a material in which a substance having a composition different from this adheres to the surface of the above positive electrode active material may be used. Examples of the surface-adhering substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0081] The above positive electrode active materials may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO 2 and LiNi 0.33 Co 0.33 Mn 0.33 O 2 Combination with ternary systems such as LiCoO 2 and LiMn 2 O 4 Or a combination of this Mn partially substituted with other transition metals, etc., or LiFePO 4 and LiCoO 2 Alternatively, a part of the Co may be replaced with another transition metal or the like.

[0082] The content of the positive electrode active material is preferably 50 to 90% by mass of the positive electrode mixture in terms of high electrochemical capacity. The content in the positive electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electrochemical capacity may be insufficient. Conversely, if the content is too high, the ionic conductivity, electronic conductivity, and electrode strength may be insufficient.

[0083] The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; Li 4 Ti 5 O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0084] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0085] The silicon-containing material includes silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, and silicon-based compounds having the general formula SiO x Silicon oxide particles represented by the formula (0.5≦x≦1.6) or a mixture thereof are preferred. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a higher capacity, and excellent cycle characteristics can be obtained.

[0086] In the present disclosure, silicon oxide is a general term for amorphous silicon oxide. Silicon oxide before disproportionation has the general formula SiO x (0.5≦x≦1.6), where x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, and then cooling and precipitating the gas.

[0087] The content of the negative electrode active material is preferably 50 to 90% by mass of the negative electrode mixture in terms of high electrochemical capacity. The content in the negative electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the negative electrode active material in the negative electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ionic conductivity, electronic conductivity, and electrode strength may be insufficient.

[0088] The electrochemical device material may be an electrolyte such as a solid electrolyte. That is, the mixture for electrochemical devices according to the first present disclosure may be an electrolyte mixture sheet containing an electrolyte, and is preferably a solid electrolyte mixture sheet containing a solid electrolyte.

[0089] The solid electrolyte may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, it has the advantage of being flexible.

[0090] The sulfide-based solid electrolyte is not particularly limited, and may be Li 2 SP 2 S 5 , Li 2 SP 2 S 3 , Li 2 SP 2 S 3 -P 2 S 5 , Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP 2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , LiI-Li 2 S-SiS 2 -P 2 S 5 , Li 2 S-SiS 2 -Li 4 SiO 4 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 3 P.S. 4 -Li 4 GeS 4 , Li 3.4 P 0.6 S 0.4 S 4 , Li 3.25 P 0.25 Ge 0.76 S 4 , Li 4-x Ge 1-x P x S 4 (x=0.6~0.8), Li4+y Ge 1-y Ga y S 4 (y = 0.2 to 0.3), LiPSCl, LiCl, Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5), Li 10 SnP 2 S 12 Any one selected from the above, or a mixture of two or more types can be used. Among them, Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) is preferred, and Li 6 PS 5 Cl is particularly preferred.

[0091] The above sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid battery that uses lithium ions as carriers, and is particularly preferred in terms of an electrochemical device having a high energy density.

[0092] In the binder sheet for an electrochemical device of the first present disclosure, the content of the above solid electrolyte is preferably 20% by mass or more, more preferably 30% by mass or more, still more preferably 40% by mass or more, and preferably 99% by mass or less, more preferably 90% by mass or less, still more preferably 85% by mass or less.

[0093] Note that the binder sheet for an electrochemical device of the first present disclosure may be an electrode binder sheet for a solid battery containing an electrode active material and a solid electrolyte.

[0094] In the binder sheet for an electrochemical device of the first present disclosure, the content of the above electrochemical device material is preferably 70% by mass or more, more preferably 80% by mass or more, still more preferably 90% by mass or more, and preferably 99.5% by mass or less, more preferably 98.5% by mass or less, still more preferably 97.5% by mass or less.

[0095] The mixture sheet for electrochemical devices according to the first present disclosure may contain a metal salt. By containing a metal salt, the ion conductivity is improved. In the mixture sheet for electrochemical devices according to the first present disclosure, the metal salt is preferably in a state of being dissolved in the silicone compound.

[0096] Any metal salt can be used as the metal salt, for example, an alkali metal salt or an alkaline earth metal salt can be used. These can be used alone or in any combination and ratio of two or more. Among them, an alkali metal salt is preferred, and a lithium salt is more preferred.

[0097] Specific examples of the lithium salt include the following: LiPF 6 , LiBF 4 , LiClO 4 , LiAlF 4 , LiSbF 6 , LiTaF 6 , LiWF 7 , LiAsF 6 , LiAlCl 4 , LiI, LiBr, LiCl, LiB 10 Cl 10 , Li 2 SiF 6 , Li 2 PFO 3 , LiPO 2 F 2 Inorganic lithium salts such as; LiWOF 5 Lithium tungstates such as: HCO 2 Li, C.H. 3 CO 2 Li, C.H. 2 FCO 2 Li, C.H.F. 2 CO 2 Li, C.F. 3 CO 2 Li, C.F. 3 CH 2 CO 2 Li, C.F. 3 CF 2 CO2 Li, C.F. 3 CF 2 CF 2 CO 2 Li, C.F. 3 CF 2 CF 2 CF 2 CO 2 Lithium carboxylates such as Li; FSO 3 Li, C.H. 3 SO 3 Li, C.H. 2 FSO 3 Li, C.H.F. 2 SO 3 Li, C.F. 3 SO 3 Li, C.F. 3 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 CF 2 SO 3 Li, lithium methyl sulfate, lithium ethyl sulfate (C 2 H 5 OSO 3 Li), lithium salts having an S=O group such as lithium 2,2,2-trifluoroethyl sulfate; Lithium bis(trifluoromethanesulfonimide) (LiTFSI), Lithium bis(monofluorosulfonimide) (LiFSI), LiN(FCO) 2 , LiN(FCO)(FSO 2 ), LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2, lithium bisperfluoroethanesulfonylimide, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, lithium cyclic 1,2-ethanedisulfonylimide, lithium cyclic 1,3-propanedisulfonylimide, lithium cyclic 1,4-perfluorobutanedisulfonylimide, LiN(CF 3 SO 2 )(FSO 2 ), LiN(CF 3 SO 2 )(C 3 F 7 SO 2 ), LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ), LiN(POF 2 ) 2 Lithium imide salts such as; LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 Lithium methide salts such as; Others, Formula: LiPF a (C n F 2n+1 ) 6-a (wherein a is an integer of 0 to 5, and n is an integer of 1 to 6) 3 (C 2 F 5 ) 3 , LiPF 3 (CF 3 ) 3 , LiPF 3 (iso-C 3 F 7 ) 3 , LiPF 5 (iso-C 3 F 7 ), LiPF 4 (CF 3 ) 2 , LiPF 4(C 2 F 5 ) 2 ), LiPF 4 (CF 3 SO 2 ) 2 , LiPF 4 (C 2 F 5 SO 2 ) 2 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiBF 3 C 3 F 7 , LiBF 2 (CF 3 ) 2 , LiBF 2 (C 2 F 5 ) 2 , LiBF 2 (CF 3 SO 2 ) 2 , LiBF 2 (C 2 F 5 SO 2 ) 2 Fluorine-containing organic lithium salts such as LiSCN and LiB(CN) 4 , LiB(C 6 H 5 ) 4 , Li 2 (C 2 O 4 ), LiP(C 2 O 4 ) 3 , Li 2 B 12 F b H 12-b (b is an integer of 0 to 3), etc.

[0098] Among them, LiTFSI, LiFSI, and LiPF 6 , LiBF 4 , LiSbF 6 , LiTaF 6 , LiPO 2 F 2 , FSO 3 Li, C.F.3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 LiTFSI, LiFSI, LiPF, etc. are preferred. 6 is particularly preferred.

[0099] These lithium salts may be used alone or in combination of two or more. A preferred example of a combination of two or more is LiPF 6 and LiBF 4 Use in combination with LiPF 6 And LiPO 2 F 2 , C 2 H 5 OSO 3 Li or FSO 3 When used in combination with Li, it has the effect of improving high-temperature storage characteristics, load characteristics, and cycle characteristics.

[0100] Another example is the combined use of an inorganic lithium salt and an organic lithium salt, which has the effect of suppressing deterioration due to high-temperature storage. 3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 etc. are preferred.

[0101] In the composite sheet for electrochemical devices according to the first present disclosure, the content of the metal salt is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, relative to the silicone compound.

[0102] The mixture sheet for electrochemical devices according to the first present disclosure may contain a conductive assistant. The conductive assistant is not particularly limited, but examples thereof include metal materials such as copper, nickel, and gold, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF, etc. These may be used alone or in any combination and ratio of two or more.

[0103] In the composite sheet for electrochemical devices according to the first present disclosure, the content of the conductive assistant is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, and even more preferably 1 mass % or more, and is preferably 30 mass % or less, more preferably 15 mass % or less, and even more preferably 5 mass % or less.

[0104] The thickness of the composite sheet for electrochemical devices according to the first present disclosure is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, and particularly preferably 150 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0105] The mixture sheet for electrochemical device according to the first embodiment of the present disclosure can be used as an electrolyte mixture sheet or an electrode mixture sheet.

[0106] The second present disclosure relates to a mixture sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, wherein the silicone compound has a polyoxyalkylene chain.

[0107] The mixture sheet for electrochemical devices according to the second disclosure can provide the same effects as the mixture sheet for electrochemical devices according to the first disclosure, and the preferred embodiments described in the mixture sheet for electrochemical devices according to the first disclosure can also be applied to the mixture sheet for electrochemical devices according to the second disclosure.

[0108] Hereinafter, the mixture sheets for electrochemical devices according to the first and second embodiments of the present disclosure will also be collectively referred to as mixture sheets for electrochemical devices according to the present disclosure.

[0109] <Method of manufacturing a composite sheet for electrochemical devices> The electrochemical device mixture sheet of the present disclosure can be obtained, for example, by a production method including a step (1) of mixing a silicone compound that is liquid at 25°C, a binder, and an electrochemical device material, and a step (2) of rolling the electrochemical device mixture obtained in the step (1) into a sheet shape. The present disclosure also relates to such a method of manufacture.

[0110] The manufacturing method of the present disclosure can provide a mixture sheet for electrochemical devices in which the silicone compound is well dispersed within the sheet, thereby enhancing the effect of imparting fluidity to electrochemical device materials by the silicone compound and further improving the sheet strength. Incidentally, the mixture sheet for electrochemical devices obtained by the production method of the present disclosure is usually not coated with the silicone compound.

[0111] The silicone compound, binder, and electrochemical device material in the above step (1) are the same as those described in the mixture sheet for electrochemical device of the present disclosure.

[0112] In the above step (1), the mixing conditions are preferably 3000 rpm or less. Preferably, the mixing speed is 10 rpm or more, more preferably 15 rpm or more, and even more preferably 20 rpm or more, and is preferably 2000 rpm or less, more preferably 1500 rpm or less, and even more preferably 1000 rpm or less. If the mixing speed is below the above range, it takes a long time to mix, which affects productivity. If the mixing speed is above the above range, excessive shear stress is applied, which may result in a mixture sheet with poor strength and flexibility.

[0113] In the above step (1), the materials may be mixed and then molded into a bulk shape. Specific methods for molding into a bulk shape include extrusion molding, press molding, and the like. In addition, the "bulk shape" does not specify a particular shape, and may be in the form of a single mass, and includes shapes such as rods, sheets, spheres, and cubes.

[0114] Specific examples of the rolling method in the above step (2) include rolling methods using a roll press, a plate press, a calendar roll machine, etc. The rolling temperature is preferably 100 to 250°C.

[0115] After the above step (2), a step (3) may be carried out in which a larger load is applied to the obtained rolled sheet to roll it into an even thinner sheet, or the step (3) may be carried out repeatedly. In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (3) is preferably 2 to 10 times, and more preferably 3 to 9 times. Specific rolling methods include, for example, a method in which two or more rolls are rotated and the rolled sheet is passed between them to process it into a thinner sheet.

[0116] It is also preferable to have a step (4) after the step (2) or the step (3) in which the rolled sheet is crushed, then formed into a bulk shape again, and rolled into a sheet. It is also preferable to repeat the step (4). The number of times of the step (4) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0117] In the above step (4), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include a method of folding the sheet, a method of forming it into a rod or thin sheet shape, a method of chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (2) or step (3) into a different shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0118] Furthermore, the step (4) may be followed by the step (3) or may be repeated. Furthermore, uniaxial or biaxial stretching may be performed in the steps (2), (3) and (4).

[0119] In the above steps (2), (3), and (4), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If it is below the above range, the number of times of rolling increases, which takes time and affects productivity. If it is above the above range, when the binder contains a fibrillating resin, fibrillation may proceed excessively, resulting in a composite sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before rolling. The sample before rolling may be a bulk-shaped raw material composition or a sheet-shaped raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling.

[0120] <Electrochemical devices> The present disclosure also relates to an electrochemical device using the mixture sheet for electrochemical devices of the present disclosure.

[0121] The electrochemical device of the present disclosure may use the mixture sheet for electrochemical devices of the present disclosure as an electrode mixture sheet, may use it as an electrolyte mixture sheet, or may use it as an electrode mixture sheet and an electrolyte mixture sheet.

[0122] The electrochemical device of the present disclosure preferably comprises a positive electrode, a negative electrode, etc., and more specifically, is preferably a secondary battery comprising these, and is particularly preferably a lithium ion secondary battery.

[0123] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0124] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0125] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0126] The positive electrode may be manufactured by a conventional method, for example, a method in which an electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0127] The density of the positive electrode mixture sheet is preferably 2.80 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0128] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0129] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0130] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0131] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0132] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0133] The secondary battery using the above-mentioned electrolyte may use electrolytes, separators, etc. that are used in known secondary batteries. These will be described in detail below.

[0134] The electrolyte is preferably a non-aqueous electrolyte, which may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.

[0135] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.

[0136] As the electrolyte salt, the above-mentioned lithium salt can be used.

[0137] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L or less.

[0138] The secondary battery using the above-mentioned electrolyte preferably further includes a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.

[0139] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.

[0140] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.

[0141] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0142] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fibrillated resin as a binder.

[0143] The material of the exterior case is not particularly limited as long as it is a material that is stable against the electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate films are preferably used.

[0144] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.

[0145] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.

[0146] The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0147] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0148] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0149] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0150] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0151] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0152] The following materials were used. All silicone compounds were liquid at 25°C. The silicone compounds were also subjected to a dehydration treatment (putting the silicone compounds in an evaporator and dissolving them in water at 1.0 x 10 2The specimen was dried for 6 hours at 130°C in an oil bath at 400°C (Pa) before use. <Silicone compounds> Silicone compound A1: KF-96-100CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25 ° C.: 100 cSt, mass loss rate when heated at 150 ° C. for 24 hours: 6.0 mass%, polyoxyalkylene chain: none, ionic conductivity when 1 mass % of LiTFSI is dissolved: 5.5 × 10 -7 S / cm, saturated moisture content: 84 ppm, moisture content after drying: 43 ppm) Silicone compound A2: KF-96L-2CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 2 cSt, mass loss rate when heated at 150°C for 24 hours: 99.9% by mass, polyoxyalkylene chain: none, ionic conductivity when 1% by mass of LiTFSI is dissolved: 1.2 × 10 -8 S / cm, saturated moisture content: 21 ppm, moisture content after drying: 11 ppm) Silicone compound A3: KF-96L-5CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 5 cSt, mass loss rate when heated at 150°C for 24 hours: 99.9% by mass, polyoxyalkylene chain: none, ionic conductivity when 1% by mass of LiTFSI is dissolved: 1.4 × 10 -8 S / cm, saturated moisture content: 20 ppm, moisture content after drying: 11 ppm) Silicone compound A4: KF-96H-60,000CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 60,000 cSt, mass loss rate when heated at 150°C for 24 hours: 0.5 mass%, polyoxyalkylene chain: none, ionic conductivity when 1 mass% of LiTFSI is dissolved: 7.4 × 10 -9 S / cm, saturated moisture content: 101 ppm, moisture content after drying: 49 ppm) Silicone compound A5: KF-96H-1,000,000 CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 1,000,000 cSt, mass loss rate when heated at 150°C for 24 hours: 0.4 mass%, polyoxyalkylene chain: none, ionic conductivity when 1 mass% of LiTFSI is dissolved: 4.8 × 10 -9 S / cm, saturated moisture content: 147 ppm, moisture content after drying: 53 ppm) Silicone compound A6: KF-96-20CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 20 cSt, mass loss rate when heated at 150°C for 24 hours: 12% by mass, polyoxyalkylene chain: none, ionic conductivity when 1% by mass of LiTFSI is dissolved: 5.8 × 10 -8 S / cm, saturated moisture content: 25 ppm, moisture content after drying: 14 ppm) Silicone compound A7: KF-96-10CS manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25°C: 10 cSt, mass loss rate when heated at 150°C for 24 hours: 31% by mass, polyoxyalkylene chain: none, ionic conductivity when 1% by mass of LiTFSI is dissolved: 5.1 x 10 -8 S / cm, saturated moisture content: 20 ppm, moisture content after drying: 10 ppm) Silicone compound B1: KF-643 manufactured by Shin-Etsu Chemical Co., Ltd. (kinetic viscosity at 25 ° C.: 19 cSt, mass loss rate when heated at 150 ° C. for 24 hours: 3.2 mass%, polyoxyalkylene chain: present, ionic conductivity when 1 mass % of LiTFSI is dissolved: 2.3 × 10 -5 S / cm, saturated moisture content: infinity, moisture content after drying: 81ppm) <Binding agent> PTFE (prepared in Preparation Example 1 below) Poly(vinylidene fluoride-co-hexafluoropropylene) (prepared in Preparation Example 2 below) Poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene) (prepared in Preparation Example 3 below) <Metal salts> Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) manufactured by Tokyo Chemical Industry Co., Ltd.

[0153] PTFE was prepared and analyzed in the following manner.

[0154] <Average primary particle diameter> The PTFE aqueous dispersion was diluted with water until the solid content became 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average primary particle diameter determined by measuring the unidirectional diameter using a transmission electron microscope were measured to prepare a calibration curve. Using this calibration curve, the average primary particle diameter was determined from the measured transmittance of the 550 nm projected light for each sample.

[0155] <Polymer solids concentration> 1 g of the PTFE aqueous dispersion is dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass (1 g) of the aqueous dispersion is expressed as a percentage and used.

[0156] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.

[0157] A white solid A was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.

[0158] (Example 1) In a 6-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 3480 g of deionized water, 100 g of paraffin wax, and 5.3 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 15.0 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 400 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached about 1200 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 310 nm, and the solid content concentration was 25.3 mass%. The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the mixture was filtered to separate the water, thereby obtaining a wet PTFE powder. The obtained wet PTFE powder was dried at 180° C. for 18 hours to obtain PTFE. The SSG of the resulting PTFE was 2.156.

[0159] (Example 2) 1650ml of pure water was put into a 3L stainless steel autoclave, and the air was replaced with nitrogen. The autoclave was pressurized slightly with hexafluoropropylene (HFP), and the temperature was adjusted to 80°C while stirring at 380 rpm. HFP was then pumped in to 0.23MPa, and a mixed monomer liquid with a molar ratio of vinylidene fluoride (VdF) and HFP of 78.2 / 21.8 was pumped in to 1.472MPa. 0.097cc of 2-methylbutane was pumped in with nitrogen, and 36.4g of ammonium persulfate dissolved in 80ml of pure water was pumped in with nitrogen to start polymerization. When the pressure dropped to 1.44MPa, the pressure was increased to 1.50MPa with continuous monomer. This was repeated for about 9.3 hours, and when 607g of continuous monomer was charged, the gas in the autoclave was released, cooled, and 2299g of dispersion was recovered. The solid content of the dispersion was 26.9wt%. Magnesium chloride was added to the dispersion to coagulate it, and then it was dried to obtain 610 g of polymer. The polymer contained HFP and VdF in a molar ratio of 22.1 / 77.9. The Mooney viscosity (ML1+10 (121°C)) of the polymer was 140, and the Tg was determined to be -18°C by DSC. No heat of fusion was observed in the second run.

[0160] (Preparation Example 3) 1500ml of pure water, CH 2 =CFCF 2 OCF(CF 3 )CF 2 OCF(CF 3 )COONH 4 0.3001g of 50% aqueous solution, C 5 F 11 COONH 4 6.001g of 50% aqueous solution was added and replaced with nitrogen, then vinylidene fluoride (VdF) was used to slightly pressurize the mixture, and the temperature was adjusted to 80°C while stirring at 600 rpm. VdF was then pressed in up to 1.22 MPa, and a mixed monomer solution of VdF and 2,3,3,3-tetrafluoropropene with a molar ratio of 77.2 / 22.8 was then pressed in up to 1.501 MPa. 0.1g of ammonium persulfate dissolved in 4ml of pure water was pressed in with nitrogen to start polymerization. When the continuous monomer reached 11g, 1,1,1,2,3,3,3-heptafluoro-2-iodo-propane 1.6738g was added. When the pressure dropped to 1.44MPa, the pressure was increased to 1.50MPa with the continuous monomer. This was repeated for about 6.2 hours, and when 521g of continuous monomer was charged, the gas in the autoclave was released, cooled, and 2087g of dispersion was recovered. The solids content of the dispersion was 26.08%. The dispersion was coagulated with calcium chloride and dried to obtain 524.3 g of polymer. The polymer contained 2,3,3,3-tetrafluoropropene and VdF in a molar ratio of 23.1 / 76.9. The Mooney viscosity (ML1+10(121°C)) of the polymer was 25, and the Tg was determined by DSC to be -14°C.

[0161] The preparation of the mixture sheet of the experimental example, the evaluation of the mixture sheet, and the evaluation of the battery were carried out according to the following procedures.

[0162] (Preparation of positive electrode mixture sheet) Active material (Experimental Examples 1 to 23: LiNi 0.8 Mn 0.1 Co 0.1 O 2 , Experimental Example 24: LiFePO4 , Experimental Example 25: LiCoO 2 ) and a conductive additive (SuperP Li: carbon black manufactured by Imerys) were weighed out, and these were placed in a V-type mixer and mixed at 37 rpm for 10 minutes to obtain a mixture of the active material and the conductive additive. Next, the mixture and the silicone compound were added to a high-speed fluid mixer and processed at 200 rpm for 1 minute to disperse the mixture. In Experimental Examples 18 to 25, the metal salt was dissolved in the silicone compound beforehand before use. Then, the weighed binder (Experimental Examples 1 to 21, 24, and 25: PTFE, Experimental Example 22: PTFE and poly(vinylidene fluoride-co-hexafluoropropylene), Experimental Example 23: PTFE and poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene)) was added to the mixture, and the mixture was cooled sufficiently in a thermostatic bath at 5°C. A mixture consisting of an active material, a conductive assistant, a binder, and a silicone compound, or a mixture consisting of an active material, a conductive assistant, a binder, a silicone compound, and a metal salt was added to a high-speed fluid mixer, and the mixture was homogenized by processing at 1500 rpm for 3 minutes. The composition ratio (mass ratio) of the active material and the conductive assistant was fixed at active material:conductive assistant=98.0:2.0, and the amount of the binder relative to the total amount of the active material, conductive assistant, and binder was set to the conditions in Tables 1 and 2. Thereafter, the mixture was sufficiently heated in a thermostatic bath at 80° C., and then treated in a high-speed fluid mixer at 2500 rpm for 8 minutes to promote fibrillation, thereby obtaining an electrode mixture. The electrode mixture was fed into a rolling machine in which metal rolls were arranged in parallel and capable of rotating at different peripheral speeds, to obtain an electrode mixture sheet (temperature: 60° C., left roll rotation speed: 1 m / min, right roll rotation speed: 0.8 m / min). The obtained electrode mixture sheet was again fed into the rolling machine and rolled to obtain an electrode mixture sheet having a stronger sheet strength. All of the obtained electrode mixture sheets were self-supporting films. Thereafter, the electrode mixture sheet was placed in a roll press machine and the gap was adjusted to a final thickness of 80 μm. Tables 1 and 2 show the contents of the silicone compound, binder, and metal salt. The content of the silicone compound is the amount relative to the solid content (active material, conductive assistant, and binder) of the electrode mixture sheet. 500 mg of the pulverized electrode mixture sheet was placed in a vial, 10 mL of a solution of hexane:acetone = 1:1 in volume ratio was added, and the mixture was stirred for 24 hours to obtain an extract. The extract was then filtered using a membrane filter (pore size 0.1 μm) and the amount present in the obtained filtrate was measured. The content of the binder is the amount relative to the solid content of the electrode mixture sheet, and the content of the metal salt is the amount relative to the silicone compound, and both are added amounts.

[0163] (Measurement of the strength of the positive electrode mixture sheet) The positive electrode mixture sheet was cut out to prepare a rectangular test piece with a width of 4 mm. A tensile tester (Shimadzu Corporation AGS-100NX) was used to measure at 100 mm / min. The chuck distance was 40 mm. Displacement was applied until breakage, and the maximum stress of the measured results was taken as the strength of each sample. Experimental Example 1 was set to 100, and evaluation was performed according to the following criteria. 10:150 and up 9:140 to under 150 8:130 to under 140 7: Between 120 and 130 6: 115 to less than 120 5: 110 to under 115 4: 105 to 110 3: 100 to 105 2:95 to under 100 Less than 1:95

[0164] (Preparation of positive electrode) The above positive electrode mixture sheet was adhered to 20 μm aluminum foil as follows. The adhesive used was a slurry of polyvinylidene fluoride (PVDF) dissolved in N-methylpyrrolidone (NMP) and carbon black dispersed in a ratio of 80:20. The adhesive was applied to aluminum foil and dried on a hot plate at 120°C for 15 minutes to form a current collector with an adhesive layer. Thereafter, the positive electrode mixture sheet was placed on a collector with an adhesive layer, and the positive electrode mixture sheet and the collector were bonded together using a roll press machine heated to 100°C. The sheet was then cut to the desired size and tabbed to form a positive electrode.

[0165] (Preparation of negative electrode) 98 parts by mass of carbonaceous material (graphite) was mixed with 1 part by mass of aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed with a disperser to form a slurry. The obtained slurry was applied to a copper foil having a thickness of 10 μm, dried, and rolled with a press machine, cut to the desired size, and tabbed to form a negative electrode.

[0166] (Preparation of electrolyte) A mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC:EMC = 30:70 (volume ratio)) was weighed into a sample bottle as an organic solvent, and fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were dissolved in it at 1 mass% each to prepare a mixed solution. LiPF 6 The salts were mixed at 23° C. to obtain a non-aqueous electrolyte.

[0167] (Preparation of aluminum laminated cell) The positive electrode was placed opposite to the negative electrode via a 20 μm-thick microporous polyethylene film (separator), and the nonaqueous electrolyte obtained above was poured into the positive electrode. After the nonaqueous electrolyte had sufficiently permeated the separator and the like, the positive electrode was sealed, precharged, and aged to prepare a lithium ion secondary battery.

[0168] <Battery evaluation> The lithium ion secondary battery produced above was charged at 45°C with a constant current-constant voltage (hereinafter referred to as CC / CV charging) to 4.25 V at a current equivalent to 0.33 C (0.1 C cut), and then discharged to 3 V at a constant current of 0.33 C, which constitutes one cycle, and the initial discharge capacity was calculated from the discharge capacity at the third cycle. The discharge capacity characteristic per unit mass of the active material (mass discharge capacity characteristic) was then calculated using the following formula. Calculation formula Mass discharge capacity characteristic (mAh / g) = initial discharge capacity (mAh) / mass of active material in the positive electrode mixture (g) The mass discharge capacity characteristics thus obtained were ranked by relative evaluation, with Experimental Example 1 being set at 100, and the evaluation was performed according to the following criteria. 7:120 and up 6: 115 to less than 120 5: 110 to under 115 4: 105 to 110 3: 100 to 105 2:95 to under 100 Less than 1:95

[0169] [Table 1] [Table 2]

[0170] (Preparation of positive electrode mixture sheet for solid state battery) Active material (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ), conductive additive (SuperP Li: carbon black manufactured by Imerys), solid electrolyte (Li 6 P.S. 5 Cl: manufactured by Sigma-Aldrich Co.) and silicone compound A1 were weighed out, and these were put into a high-speed fluid mixer and processed at 200 rpm for 1 minute to obtain a mixture consisting of the active material, conductive assistant, solid electrolyte, and silicone compound. Then, a weighed amount of binder (fibrillar resin: PTFE powder) was added to the mixture, and the mixture was thoroughly cooled in a thermostatic bath at 5°C. A mixture of active material, conductive assistant, solid electrolyte, binder, and silicone compound was added to a high-speed fluid mixer, and the mixture was homogenized by processing at 1500 rpm for 3 minutes. The composition ratio (mass ratio) of the active material, conductive assistant, binder, and solid electrolyte was active material:conductive assistant:binder:solid electrolyte:silicone compound A1=66.5:2:1.5:30:3. Thereafter, the mixture was sufficiently heated in a thermostatic bath at 80° C., and then treated in a high-speed fluid mixer at 2500 rpm for 8 minutes to promote fibrillation, thereby obtaining an electrode mixture. The electrode mixture was fed into a rolling machine in which metal rolls were arranged in parallel and capable of rotating at different peripheral speeds to obtain a positive electrode mixture sheet (temperature: 60° C., left roll rotation speed: 1 m / min, right roll rotation speed: 0.8 m / min). The obtained positive electrode mixture sheet was again put into the rolling machine and rolled to obtain a positive electrode mixture sheet having a stronger sheet strength. Thereafter, the positive electrode mixture sheet was placed in a roll press machine and the gap was adjusted to a final thickness of 85 μm. The obtained positive electrode mixture sheet was a self-supporting film.

[0171] (Preparation of solid electrolyte mixture sheet for solid-state battery: Experimental example 26) Solid electrolyte (Li 6 P.S. 5 Cl: manufactured by Sigma-Aldrich Co.) and silicone compound A1 were weighed out, and these were put into a high-speed fluid mixer and processed at 200 rpm for 1 minute to obtain a mixture consisting of a solid electrolyte and a silicone compound. Then, a weighed amount of binder (fibrillar resin: PTFE powder) was added to the mixture, and the mixture was thoroughly cooled in a thermostatic bath at 5°C. The mixture consisting of the binder, solid electrolyte, and silicone compound was added to a high-speed fluid mixer, and homogenized by processing at 1500 rpm for 3 minutes. The composition ratio (mass ratio) of the binder, solid electrolyte, and silicone compound was binder:solid electrolyte:silicone compound=1.5:98.5:3. Thereafter, the mixture was sufficiently heated in a thermostatic bath at 80° C., and then treated in a high-speed fluid mixer at 2500 rpm for 8 minutes to promote fibrillation, thereby obtaining a solid electrolyte mixture. The solid electrolyte mixture was fed into a rolling machine in which metal rolls were arranged in parallel and capable of rotating at different peripheral speeds, to obtain a solid electrolyte mixture sheet (temperature: 60°C, left roll rotation speed: 1 m / min, right roll rotation speed: 0.8 m / min). The obtained solid electrolyte mixture sheet was again put into the rolling machine and rolled to obtain a solid electrolyte mixture sheet having a higher sheet strength. Thereafter, the solid electrolyte mixture sheet was placed in a roll press machine and the gap was adjusted to a final thickness of 45 μm. The solid electrolyte mixture sheet was a self-supporting membrane.

[0172] (Fabrication of solid-state batteries) After the prepared positive electrode and solid electrolyte layer were punched, the positive electrode and a lithium foil serving as a negative electrode were placed opposite each other, laminated with the solid electrolyte layer in between, and pressed to integrate them into a solid-state battery.

[0173] (Preparation of solid electrolyte mixture sheet for solid-state battery by coating method: Experimental example 27) Solid electrolyte (Li 6 P.S. 5 Cl: manufactured by Sigma-Aldrich Co.) and silicone compound A1 were weighed out, and these were put into a high-speed fluid mixer and processed at 200 rpm for 1 minute to obtain a mixture consisting of a solid electrolyte and a silicone compound. Separately, the binder obtained in Preparation Example 3 was dissolved in butyl butyrate to obtain a 5 wt% binder solution, which was added to the mixture and mixed for 2 minutes at 2000 rpm using a planetary centrifugal mixer to obtain a solid electrolyte slurry composition. The composition ratio (mass ratio) of the binder, solid electrolyte, and silicone compound was set to binder:solid electrolyte:silicone compound=30:70:3. The obtained solid electrolyte slurry composition was applied onto a PET film using a doctor blade (gap 80 μm), dried in a drying oven at 100° C. for 12 hours, and then placed in a roll press machine and the gap was adjusted to adjust the final thickness of the solid electrolyte layer to 50 μm. Thereafter, the solid electrolyte layer was peeled off from the PET film to obtain a self-supporting solid electrolyte mixture sheet.

[0174] (Fabrication of solid-state batteries) After the prepared positive electrode and solid electrolyte layer were punched, the positive electrode and a lithium foil serving as a negative electrode were placed opposite each other, laminated with the solid electrolyte layer sandwiched therebetween, and pressed to integrate them to prepare a solid-state battery.

[0175] (Strength measurement of solid electrolyte mixture sheet) The solid electrolyte mixture sheet was cut out to prepare a rectangular test piece having a width of 4 mm. A tensile tester (AGS-100NX manufactured by Shimadzu Corporation) was used to measure at a speed of 100 mm / min. The distance between the chucks was 40 mm. Displacement was applied until breakage, and the maximum stress of the measured results was taken as the strength of each sample. Experimental Example 1 was set to 100, and the samples were evaluated according to the following criteria. The results are shown in Table 3. 10:150 and up 9:140 to under 150 8:130 to under 140 7: Between 120 and 130 6: 115 to less than 120 5: 110 to under 115 4: 105 to 110 3: 100 to 105 2:95 to under 100 Less than 1:95

[0176] <Battery evaluation> The solid-state battery produced above was charged at 45°C with a constant current-constant voltage (hereinafter referred to as CC / CV charging) to 4.25 V at a current equivalent to 0.33 C (0.1 C cut), and then discharged to 3 V at a constant current of 0.33 C, which constitutes one cycle, and the initial discharge capacity was calculated from the discharge capacity at the third cycle. The discharge capacity characteristic per unit mass of the active material (mass discharge capacity characteristic) was then calculated using the following formula. Calculation formula Mass discharge capacity characteristic (mAh / g) = initial discharge capacity (mAh) / mass of active material in the positive electrode mixture (g) The mass discharge capacity characteristics thus obtained were ranked by relative evaluation, and were evaluated according to the following criteria, with Experimental Example 1 being set at 100. The results are shown in Table 3. 7:120 and up 6: 115 to less than 120 5: 110 to under 115 4: 105 to 110 3: 100 to 105 2:95 to under 100 Less than 1:95

[0177] [Table 3]

Claims

1. A composite sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, the content of the silicone compound is 0.5 to 20 mass% based on the solid content of the electrochemical device mixture sheet, The silicone compound has a kinetic viscosity at 25° C. of 5 cSt to 60,000 cSt.

2. 2. The mixture sheet for electrochemical devices according to claim 1, wherein the silicone compound has a polyoxyalkylene chain.

3. 3. The mixture sheet for electrochemical devices according to claim 1, wherein the content of the silicone compound is 0.5 to 15 mass % based on the solid content of the mixture sheet for electrochemical devices.

4. A composite sheet for electrochemical devices, comprising a silicone compound that is liquid at 25° C., a binder, and an electrochemical device material, The silicone compound has a polyoxyalkylene chain.

5. 5. The composite sheet for electrochemical devices according to claim 1, wherein the silicone compound has a saturated moisture content at 25[deg.] C. of more than 30 ppm.

6. 5. The composite sheet for electrochemical devices according to claim 1, wherein the silicone compound has a mass loss rate of 20 mass % or less when heated at 150° C. for 24 hours.

7. 5. The mixture sheet for electrochemical devices according to claim 1, wherein the content of the binder is 0.5 to 10 mass % based on the solid content of the mixture sheet for electrochemical devices.

8. The mixture sheet for an electrochemical device according to claim 1 or 4, which contains a metal salt.

9. 9. The mixture sheet for electrochemical devices according to claim 8, wherein the content of the metal salt relative to the silicone compound is 0.1 to 30% by mass.

10. 5. The mixture sheet for electrochemical devices according to claim 1, wherein the mixture sheet for electrochemical devices is an electrode mixture sheet or an electrolyte mixture sheet.

11. 5. The composite sheet for electrochemical devices according to claim 1, wherein the binder is a fluorine-containing polymer material.

12. The electrochemical device mix sheet according to claim 11, wherein the binder is at least one selected from the group consisting of polytetrafluoroethylene, poly(vinylidene fluoride-co-hexafluoropropylene) and poly(vinylidene fluoride-co-2,3,3,3-tetrafluoropropylene).

13. 13. The mixture sheet for electrochemical devices according to claim 12, wherein the binder is polytetrafluoroethylene.

14. The mixture sheet for electrochemical devices according to claim 1 or 4, further comprising a conductive assistant.

15. 5. An electrochemical device using the mixture sheet for electrochemical devices according to claim 1 or 4.

16. (1) mixing a liquid silicone compound, a binder, and an electrochemical device material at 25° C.; and (2) rolling the mixture for use in electrochemical devices obtained in the step (1) into a sheet.

17. The silicone compound has a kinematic viscosity at 25° C. of 5 cSt to 60,000 cSt; The silicone compound has a polyoxyalkylene chain, The method according to claim 16, wherein the binder is polytetrafluoroethylene.

Citation Information

Patent Citations

  • Negative electrode paste of lithium ion battery and lithium ion battery

    CN106531963A

  • Anode plate, secondary battery thereof and preparation method

    CN109326767A

  • Polymer gel electrolyte and lithium battery using it

    JP2002151150A

  • Binder composition for secondary battery electrode, slurry for secondary battery electrode and secondary battery electrode

    JP2006260821A

  • Lithium secondary battery and method of manufacturing lithium secondary battery

    JP2007173026A